Primitive Communism Is Not What It Used to Be : At the Origin of Male Domination - Darmangeat, Christophe, (Historical Materialism Book Series ;, 2024)
When was male domination established in human societies, and why did it take hold? How does humanity's most remote past inform today's feminist struggle? This new, updated edition of Primitive Communism Is Not What It Used to Be - available for